2023
DOI: 10.1007/s12020-023-03413-8
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status and its association with prevalence of thyroid diseases in adults from Jiangxi Province, China

Di-en Yan,
Lei Hu,
Yun-feng Shen
et al.

Abstract: Background: Iodine is an essential element for biosynthesis of thyroid-stimulating hormone (TSH). Both excessive and de ciency of iodine are major risk factor for thyroid diseases, including thyroid dysfunction, thyroid nodules, and thyroid autoimmunity (TAI). This study aimed to elucidate the relationship between iodine status and incidence of thyroid diseases through a national cross-sectional epidemiological survey (TIDE) in Jiangxi province (China).Methods: A population-based, cross-sectional study enrolle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, China launched a mandatory universal salt iodization program in 1996, which has been efective in controlling thyroid-related diseases [12]. However, recent studies also suggested that excessive iodine intake may increase the risk of thyroid nodules [12][13][14]. Tus, there is an urgent need to identify several additional modifable risk factors, especially key factors, in adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, China launched a mandatory universal salt iodization program in 1996, which has been efective in controlling thyroid-related diseases [12]. However, recent studies also suggested that excessive iodine intake may increase the risk of thyroid nodules [12][13][14]. Tus, there is an urgent need to identify several additional modifable risk factors, especially key factors, in adults.…”
Section: Introductionmentioning
confidence: 99%